Physical simulation of upper protective coal layer mining with different coal seam inclinations - Feng Fang; Cai Shu; Hongtu Wang (Energy Science & Engineering, 2020)
Abstract Protective coal layer (PCL) mining is a preferred regional method for preventing coal and gas outbursts; stress‐relief of PCL mining is the prerequisite of pressure‐relief gas drainage. In order to study the stress‐relief effect of PCL mining on protected coal seams and determine the protection scope of PCL mining under different inclinations, this paper uses physical simulations to study the stress‐relief law and deformation characteristics of the strata during upper PCL mining with a gentle inclination (25°), an intermediate inclination (45°), and a steep inclination (65°). The results show that as the coal seam dip increases, the degree of deformation and failure of the overburden strata gradually decreases, the severe subsidence and expansion area of the overburden strata tends to gradually develop in the uphill direction of the working face, and the floor strata underlying the protective seam significantly expand toward the goaf. However, the absolute value of the upward movement of the floor strata is much smaller than that of the roof strata; and the greater the dip angle, the greater the ratio of floor displacement to roof subsidence. The stress‐relief curve of the protected layer is approximately U‐shaped. As the inclination of the coal seam increases, the stress‐relief range decreases gradually. The maximum relief‐stress and the stress release coefficient of the protected layer initially increase and then decrease. The stress concentration coefficient of the protected coal seam initially increases first and then decreases in both uphill and downhill of the working face in the PCL. As the inclination increases, the stress‐relief angle of the downhill boundary initially increases and then decreases, while the stress‐relief angle of the uphill boundary decreases gradually. Our research results provide guidance for the delimitation of the protected scope of PCLs with different dip angles.